Collaborative knowledge management application support teaching and learning environment - Abdullah, Rusli (2007)
The power of Knowledge Management System (KMS) or application is no longer possesses any limitation. In fact, many KMS practitioners have claimed it as the most desired and demanded energizer to the organizations today, as the role it plays is absolutely important. This role of KMS could be determined by looking on the issues of how to ens,ure that the right knowledge could be disseminated to the right people at the right time. This paper is a partial of report of our research in KMS that analyzes the concept, system and architectural of collaborative KMS in teaching and learning environment of a learning organization (LO). In order to ensure the outcome of research analysis that has been done in a proper way, a system prototype of the KMS with agent technology capability was developed and implemented at the selected domain that served LO community as a case study. This paper also discusses various issues involved in this field that will help any LO to' increase their productivity and quality as well as to gain return on investment (ROI).